EU Challenges, Investment in the EU and the Role of the European Investment Group - Debora Revoltella (Intereconomics, 2016)
While monetary policy is close to the limits of what it can achieve, consensus on a more active fiscal policy is still lacking. Indeed, on the political front, Europe stands at something of a political crossroads, facing growing social, economic and political challenges. Efforts are now focused on pragmatically advancing on key common priorities. The urgency and ambition with which this co-operation proceeds will be critical to success.
Keywords: 330